Complex duodenal fistulae: a surgical nightmare - Ari Leppäniemi; Matti Tolonen; Panu Mentula (World Journal of Emergency Surgery, 2023)
Abstract Introduction A common feature of external duodenal fistulae is the devastating effect of the duodenal content rich in bile and pancreatic juice on nearby tissues with therapy-resistant local and systemic complications. This study analyzes the results of different management options with emphasis on successful fistula closure rates. Methods A retrospective single academic center study of adult patients treated for complex duodenal fistulas over a 17-year period with descriptive and univariate analyses was performed. Results Fifty patients were identified. First line treatment was surgical in 38 (76%) cases and consisted of resuture or resection with anastomosis combined with duodenal decompression and periduodenal drainage in 36 cases, rectus muscle patch, and surgical decompression with T-tube in one each. Fistula closure rate was 29/38 (76%). In 12 cases, the initial management was nonoperative with or without percutaneous drainage. The fistula was closed without surgery in 5/6 patients (1 patient died with persistent fistula). Among the remaining 6 patients eventually operated, fistula closure was achieved in 4 cases. There was no difference in successful fistula closure rates among initially operatively versus nonoperatively managed patients (29/38 vs. 9/12, p = 1.000). However, when considering eventually failed nonoperative management in 7/12 patients, there was a significant difference in the fistula closure rate (29/38 vs. 5/12, p = 0.036). The overall in-hospital mortality rate was 20/50 (40%). Conclusions Surgical closure combined with duodenal decompression in complex duodenal leaks offers the best chance of successful outcome. In selected cases, nonoperative management can be tried, accepting that some patients may require surgery later.